Bibliometric analysis and citation networks visualization of the theses from 2005 to 2017 of the University of the Philippines Population Institute Library - Abang, Christian Jude V.; Pascua, Sonia M. (Quezon City School of Library and Information Studies, University of the Philippines, 2018)
A bibliometric analysis was performed on the theses at the University of the Philippines Population Institute Library from 2005 to 2017 to analyze the collection. Also, the author and citation networks were visualized to gain knowledge of the interconnections between the theses through its citations. The researcher also intends to create a citation index based on the standard citation format of the institution, which is in APA format. Various tools were considered and evaluated, in which R was selected. Through the use of the tools, as well as the citations collected during data gathering, the data were processed and analyzed. Results indicate the year of publication of the citations used, the most cited authors, journals, and specific titles, as well as the types of publications cited. The journal trend throughout the years was also determined. Through the visualization produced, communities within the networks were identified, along with its authors, and its corresponding subject fields. The results were then analyzed and interpreted, from which conclusions were generated.
Thesis
Keywords: Bibliometrics -- Philippines